Trade and Country Legislation as a Roadmap for Economic Integration: Focus on Balkan Countries - Mehmeti, Ismail A; Krasniqi, Sokol; Sogojeva, Hysen (International Journal of Management Excellence (ISSN: 2292-1648), 2020)
Purpose: This paper focuses on identifying the role of trade and legislation of a country for economic integration. Every Balkan country has claims to integrate into the large family of the European Union- EU. This context besides foreign trade legal infrastructure is one of the main determinants of this process. It is imperative that laws related to the process of economic integration should comply with EU legal directives. Design/Methodology/Approach: Data processing design (for legislation as a roadmap for economic integration) is in line with established international standards. It focuses on data published by the governing institutions of the relevant countries using deductive methods. It also compares data obtained from research in analytical and synthetic terms with direct access to literature, scientific journals, as well as official reports published locally and abroad. Findings: Today, economic integration has become a necessity of recent times. They are influenced by a large number of relevant factors and are received by political actors on the basis of whose political actions will bring about liberal or protectionist policies. Each state has its own legal acts and other legal provisions regulating the functioning of the country's legal system. Free trade and the implementation of economic integration are closely linked to "Fiscal Policy" as part of the overall economic system. Adoption of restrictive fiscal laws that impede the international movement of goods and services has detrimental effects on the development of international trade and impedes the development of good relations between sovereign states. Practical Implications: The elaboration of this paper is based on the legal analysis of contemporary economic integration as well as the economic aspects and modalities for the practical realization of regional integration. The paper presents data - on market performance and legislation that determines economic integration - which shows the current state of affairs of the Western Balkan countries in the context of such integration. Originality/Value: The data in the paper present the real state of commercial economic developments and legislation as determinant of economic integration in the Western Balkan countries. The focus is on the creation of adjacent legislative spaces of these countries, which enables accelerated integration with the ultimate aim of joining the EU.